MORPHOLOGICAL CHANGES OF RATS’ PERIPHERAL NERVE AFTER 6 WEEKS IN THE CONDITIONS OF ITS DAMAGE AND PHARMACOLOGICAL CORRECTION - Demidchuk, A.S. (World of Medicine and Biology, 2015)
Pathology of peripheral nervous system is one of the most common in neurological practice. It is almost half the adult neurological disease. The range of diseases of the peripheral nervous system is very wide. Conservative means of pharmacological treatment in the primary stages of rehabilitation does not lead to the full restoration of the lost limb function. Thus it is appropriate to continue the search for pharmacological agents that effectively would impact on key regeneration of injured peripheral nerves. The purpose of this research was to study ultrastructure changes of rats’ peripheral nerve in the conditions of its damage and neuropeptides application and without pharmacological correction in 6 weeks after trauma. Research was conducted on white rats which were devided into three groups. In animals of the I, II and III groups the experimental model of sciatic nerve trauma was done. In postoperative period the rats of the first group had any pharmacological correction. The second group rats received сerebrolysinum in the dose of 0,02 mg/kg daily during 21 day postoperatively, the third the group animals received сerebralum in the dose of 0,02 mg/kg daily during three days postoperatively. Morfology study of the rat’s sciatic nerve peripheral stump in 6 weeks after trauma in all three groups of animals was done by electron microscopic methods. For the purpose of microscopy light optical histological material was fixed in 10% solution of neutral formalin, washed and treated samples in cryostat sections, which later imprehnetion solution of silver nitrate impregnation method for rapid elements peryferichnoyi nervous system (Kolomyitsev AK et al., 1981 ). Thus, studies of the damaged nerve six weeks after the injury indicates injury all areas of the injured nerve. Application cerebrolysin leads to a partial regeneration of nerve fibers and reducing two types of inflammatory processes. Together with those most effective treatment of damaged nerve occurs when using tserebralu as regenerate nerve fibers of two types in large numbers.